Sociology in the Pocket - Nedeljković, Radica M. (Sociološki pregled, 2018)
Dragoljub B. Đorđević, Pocket Sociology for Beginners, 1.issue in 2016. Novi Sad: Prometej, Niš, University in Niš - Faculty of Mechanical Engineering, 2.issue in 2017. Niš, University of Niš - Faculty of Mechanical Engineering, 175p.